2018
DOI: 10.1074/jbc.ra118.004169
|View full text |Cite
|
Sign up to set email alerts
|

Glyceraldehyde-3-phosphate dehydrogenase is a chaperone that allocates labile heme in cells

Abstract: Cellular heme is thought to be distributed between a pool of sequestered heme that is tightly bound within hemeproteins and a labile heme pool required for signaling and transfer into proteins. A heme chaperone that can hold and allocate labile heme within cells has long been proposed but never been identified. Here, we show that the glycolytic protein glyceraldehyde-3-phosphate dehydrogenase (GAPDH) fulfills this role by acting as an essential repository and allocator of bioavailable heme to downstream protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
144
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(155 citation statements)
references
References 48 publications
11
144
0
Order By: Relevance
“…PQQ is synthesized in the cytosol, but the proteins that use it are periplasmic . It is unknown how PQQ gets to the periplasm, but the reactivity of PQQ with nucleophiles at its C5 position would likely necessitate a chaperoned process, as is the case for other reactive enzyme cofactors such as heme and iron–sulfur clusters …”
Section: Resultsmentioning
confidence: 99%
“…PQQ is synthesized in the cytosol, but the proteins that use it are periplasmic . It is unknown how PQQ gets to the periplasm, but the reactivity of PQQ with nucleophiles at its C5 position would likely necessitate a chaperoned process, as is the case for other reactive enzyme cofactors such as heme and iron–sulfur clusters …”
Section: Resultsmentioning
confidence: 99%
“…However, the molecules and mechanisms that mobilize heme from its site of synthesis are not well defined. Recent work supports the role of a number of proteins in this distribution, including glyceraldehyde phosphate dehydrogenase (GAPDH) [91,92], PGRMC1 [83] and PGRMC2 [90]. Further, it is unclear how the demand for heme in different cellular locations regulates the distribution of heme from FECH.…”
Section: Ferrochelatasementioning
confidence: 99%
“…The heme trafficking kinetics data challenge the current conceptual paradigm for the cellular distribution of mitochondrial heme. The discovery of the first putative mitochondrial heme exporter, Flvcr1b, the only mitochondrial heme transporter identified to date (Chiabrando et al, 2012), has often been taken to imply that heme distribution is sequential, with heme first transported into the cytosol followed by its mobilization to other organelles (Hanna et al, 2017; Reddi and Hamza, 2016; Sweeny et al, 2018). However, we found that heme distribution to the mitochondrial matrix, cytosol, and nucleus occurs virtually simultaneously, suggesting the existence of parallel pathways for heme mobilization to different cellular locales ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, using genetically encoded ratiometric fluorescent h eme s ensors (HS1) targeted to the mitochondrial matrix, cytosol, or nucleus (Hanna et al, 2016; Hanna et al, 2018; Sweeny et al, 2018), we developed a live-cell assay in yeast to monitor heme distribution kinetics to probe the role of ALAS and ER-mitochondrial contact sites and dynamics on subcellular heme trafficking. Surprisingly, we find that heme trafficking rates from the matrix side of the IM to the mitochondrial matrix and cytosol are similar, while trafficking to the nucleus is ∼25% faster.…”
Section: Introductionmentioning
confidence: 99%